2020
DOI: 10.1111/nhs.12777
|View full text |Cite
|
Sign up to set email alerts
|

Professional identity of allied health staff associated with a major health network organizational restructuring

Abstract: Maintenance of professional identity, particularly during periods of organizational restructuring, is critical within modern complex healthcare systems as professional identity contributes to the psychological well-being of staff and leaders. This study aimed to evaluate change in professional identity of allied health staff associated with a major health network organizational restructuring in Australia. Data were collected from allied health staff in 2017 and 2019, before (n = 226) and after (n = 197) the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Forty-five studies (28%) were concerned with the political, social and healthcare reforms and advances. This included the impact on professional identity (35 or 22%) (Bertin & Pantalone, 2019 ; Blomberg, 2016 ; Bludau, 2017 ; Bochatay, 2018 ; Brunton, 2017 ; Carpenter & Platt, 1997 ; Cascón-Pereira et al, 2016 ; Currie et al, 2010 ; Dahl & Clancy, 2015 ; de Meis et al, 2007 ; Feen-Calligan, 2012 ; Frechette et al, 2020 ; Furtaw, 2004 ; Gent, 2017 ; Gomaa, 1999 ; Handy et al, 2020 ; Hendrikx, 2018 ; Hurley, 2009 ; Iglesias & De Bengoa Vallejo, 2011 ; Kyratsis et al, 2017 ; Larsson et al, 2009 ; McMurray & Pullen, 2008 ; Mishra et al, 2012 ; O’Shea & McGrath, 2019 ; Ocek & Vatansever, 2014 ; Piil et al, 2012 ; Porter & Wilton, 2019 ; Sanders, 2019 ; Snelgrove, 2009 ; Takashima & Saeki, 2019 ; Thompson, 2005 ; Thomson et al, 2014 ; Vincifori & Molinar, 2014 ; Wiles & Vicary, 2019 ; Zufferey, 2012 ), the role of professional identity in adjusting to these reforms or advances (8) (Bertrand, 2009 , 2010 ; Dadich et al, 2015 ; Deppoliti, 2003 ; Franco & Tavares, 2013 ; Gregg & Magilvy, 2001 ; Hammond et al, 2016 ; Wright, 2007 ) as well as the broader impact of political and social reform on recruitment and retention of health care workers through professional identity effects (2) (Allen, 2011 ; Deppoliti, 2008 ).…”
Section: Results (Step 5)mentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-five studies (28%) were concerned with the political, social and healthcare reforms and advances. This included the impact on professional identity (35 or 22%) (Bertin & Pantalone, 2019 ; Blomberg, 2016 ; Bludau, 2017 ; Bochatay, 2018 ; Brunton, 2017 ; Carpenter & Platt, 1997 ; Cascón-Pereira et al, 2016 ; Currie et al, 2010 ; Dahl & Clancy, 2015 ; de Meis et al, 2007 ; Feen-Calligan, 2012 ; Frechette et al, 2020 ; Furtaw, 2004 ; Gent, 2017 ; Gomaa, 1999 ; Handy et al, 2020 ; Hendrikx, 2018 ; Hurley, 2009 ; Iglesias & De Bengoa Vallejo, 2011 ; Kyratsis et al, 2017 ; Larsson et al, 2009 ; McMurray & Pullen, 2008 ; Mishra et al, 2012 ; O’Shea & McGrath, 2019 ; Ocek & Vatansever, 2014 ; Piil et al, 2012 ; Porter & Wilton, 2019 ; Sanders, 2019 ; Snelgrove, 2009 ; Takashima & Saeki, 2019 ; Thompson, 2005 ; Thomson et al, 2014 ; Vincifori & Molinar, 2014 ; Wiles & Vicary, 2019 ; Zufferey, 2012 ), the role of professional identity in adjusting to these reforms or advances (8) (Bertrand, 2009 , 2010 ; Dadich et al, 2015 ; Deppoliti, 2003 ; Franco & Tavares, 2013 ; Gregg & Magilvy, 2001 ; Hammond et al, 2016 ; Wright, 2007 ) as well as the broader impact of political and social reform on recruitment and retention of health care workers through professional identity effects (2) (Allen, 2011 ; Deppoliti, 2008 ).…”
Section: Results (Step 5)mentioning
confidence: 99%
“…Seventy-three studies of 103 studies were classified as Social in three subcategories. Thirty studies were identified as being focussed on group membership in their investigation (Barbour & Lammers, 2015 ; Bochatay, 2018 ; Brosnan & Cribb, 2019 ; Carrillo & Rubel, 2019 ; Croft et al, 2015a , 2015b ; Curtis & Day, 2013 ; Elvey et al, 2013 ; Feen-Calligan, 2012 ; Findlow, 2012 ; Franco & Tavares, 2013 ; Gregg & Magilvy, 2001 ; Hammond et al, 2016 ; Koskiniemi et al, 2019 ; Kyratsis et al, 2017 ; Lafleur, 2007 ; Lévesque et al, 2019 ; McCrae et al, 2014 ; Mellin et al, 2011 ; Meyer et al, 2015 ; Moorhead et al, 2016 ; Moorhead, 2019 ; Mousazadeh et al, 2019 ; Niemi & Paasivaara, 2007 ; Porter & Wilton, 2019 ; Reyes Villagomeza, 2019 ; Sabanciogullari & Dogan, 2017 ; Stone et al, 2002 ; Tahim, 2015 ; Thomson et al, 2014 ) whilst 28 studies focussed on role (Baathe & Norbäck, 2013 ; Dadich et al, 2015 ; Diede, 2018 ; Fleit, 2008 ; Frechette et al, 2020 ; Handy et al, 2020 ; Hansen et al, 2019 ; Hanson, 2009 ; Hazen et al, 2018 ; Hendrikx, 2018 ; Iglesias & De Bengoa Vallejo, 2011 ; Kumpusalo et al, 1994 ; Kunhunny & Salmon, 2017 ; Landis et al, 2020 ; Martin et al, 2020 ; McKenzie & Williamson, 2016 ; Pape et al, 2018 ; Piil et al, 2012 ; Pottie et al, 2009 ; Pratt et al, 2006 ; Salim & Elgizoli, 2016 ; Sanders,…”
Section: Results (Step 5)mentioning
confidence: 99%
“…Furthermore, to date, most healthcare reforms are typically led by physicians and nurses (Voyer, 2013), whereas the voices of allied healthcare staff leaders (e.g., dietitians, physiotherapists) have hardly been heard. This is surprising, as allied healthcare staff represent one quarter of the health workforce and are not immune to organizational reforms (Porter & Wilton, 2020).…”
mentioning
confidence: 99%
“…Allied health staff are faced with a range of unique challenges that predicates a need for more targeted research. Some of these challenges include navigating multiple identities with respect to their profession, the overarching allied health structure and to their interprofessional teams (Porter and Wilton, 2020). Further challenges reported by Mak et al (2019) included AHPs perceptions of medical dominance and a lack of professional recognition within the healthcare context which was impacting their job satisfaction.…”
Section: Introductionmentioning
confidence: 99%